Pelatihan Visualisasi Molekul Kimia dengan Software Chemsketch bagi Peserta didik SMA di Kota Kupang NTT - Sudirman Sudirman; Jasman .; I Gusti M.N. Budiana; Dewi Lestarani; Eka Citra G. Kerihi; Yusnaeni . (Universitas Nusa Cendana, 2023)
The problems in learning chemistry faced by teachers at school include: (1) how to visualize chemical molecular structures that are still manual, namely drawing on whiteboards or sometimes with the Microsoft Word program which is familiar to most students will give results that are not in accordance with the rules of writing symbols; (2) the aspect of the teacher's and students' lack of insight regarding the Chemsketch software for drawing chemical molecular structures; and (3) aspects of students' enthusiasm and interest in self-development which are still limited. Of all the problems faced by partners, the solution offered is a Chemical Molecule Visualization Training activity with Chemsketch Software for High School Students in Kupang City, NTT. With this training, students are expected to have knowledge and skills in using Chemsketch Software in drawing chemical molecular structures and attracting students' learning interest and arousing students' curiosity through observing the material displayed through visualization of chemical molecular shapes.